Tunable anomalous Hall conductivity through volume-wise magnetic competition in a topological kagome magnet - Z. Guguchia (Nature Portfolio, 2020)
The kagome magnet Co3Sn2S2 has complex magnetic behaviour and a topological band structure that yields a large anomalous Hall effect. Guguchia et al. find phase separation between ferro- and anti-ferromagnetic orders and that the volume-wise competition controls the anomalous Hall conductivity